BRAF V600E Status and Stimulated Thyroglobulin at Ablation Time Increase Prognostic Value of American Thyroid Association Classification Systems for Persistent Disease in Differentiated Thyroid Carcinoma. (7th April 2019) - Repaci, Andrea; Vicennati, Valentina; Paccapelo, Alexandro; Cavicchi, Ottavio; Salituro, Nicola; Monari, Fabio; de Biase, Dario; Tallini, Giovanni; Altimari, Annalisa; Gruppioni, Elisa; Fiorentino, Michelangelo; Pagotto, Uberto
Abstract : Background . Stimulated thyroglobulin levels measured at the time of remnant ablation (A-hTg) and BRAF V600E mutation had shown prognostic value in predicting persistent disease in differentiated thyroid cancer (DTC). The aim of this study was to evaluate the prognostic role of A-hTg combined with the BRAF V600E status in association with the revised American Thyroid Association (ATA) risk stratification. Material and Methods . 620 patients treated for a DTC were included in this study with a median follow-up duration of 6.1 years. All patients underwent total thyroidectomy followed by radioiodine ablation. Patients with positive anti-thyroglobulin antibodies were excluded. The predictive value of A-hTg was calculated by receiver operating characteristic curve (ROC curve) analysis. The Cox proportional hazard regression model, including the BRAF status, A-hTg, and ATA classification system, was assessed to evaluate the existing persistent disease risk. Results . Taken together, the BRAF status and A-hTg levels improve the ATA risk classification in all categories. In particular, in the low-risk ATA classification, only the combination of BRAF V600E +A-hTg > 8.9 ng/ml was associated with persistent disease (P = 0.001, HR 60.2, CI 95% 5.28-687). In the intermediate-risk ATA classification, BRAF WT +A-hTg > 8.9 ng/ml was associated with persistent disease (P = 0.029, HR 2.71, CI 95% 1.106-6.670) and BRAF V600E +A-hTg > 8.9 ng/ml was also associated with persistent disease (P < 0.001, HR 5.001, CI 95% 2.318-10.790). In the high-risk ATA classification, both BRAF V600E +A-hTg < 8.9 ng/ml and BRAF V600E +A-hTg > 8.9 ng/ml were associated with persistent disease (P = 0.042, HR 5.963, CI 95% 1.069-33.255 andP = 0.002, HR 11.564, CI 95% 2.543-52.576, respectively). Conclusions . The BRAF status and stimulated thyroglobulin levels at ablation time improve the ATA risk stratification of differentiated thyroid cancer; therefore, even A-hTg could be included in risk classification factors.